The Impact of Debt and Interest Rates on the Discount and Premium to NAV : Empirical Evidence from Listed Swedish Real Estate Companies Between 2012 and 2023 - Suutari, Valtteri (My University, 2024)
The discount and premium to net asset value (NAV) is a widely recognized phenomenon in which listed real estate companies trade below (discount) or above (premium) their NAV. This indicates that the indirect market perceives the company’s underlying assets as less or more valuable than the direct market. A multitude of factors is known to influence the NAV valuation. This thesis focuses on how debt, with debt-to-equity as a proxy, and interest rates affect it. These variables are significant because leverage is fundamental to the business model of real estate companies. At the same time, interest rates directly impact debt capital markets and, consequently, the leverage ratios of these firms. While previous literature has shown a negative relationship between debt and discount to NAV, evidence regarding interest rates remains limited, with no recent studies focused on the Swedish listed real estate market. This thesis consists of a literature review and an empirical study. The literature review examines the relevant research on the discount to NAV and what factors have proven to affect it, e.g., debt, liquidity, market capitalization, and market sentiment to name a few. Additionally, the literature review goes over the valuation of direct and indirect real estate so the reader understands the underlying dynamics of how a company’s NAV is derived. The empirical analysis employs a fixed effects regression model to examine the effects of debt and interest rates on NAV. To account for other influencing factors, liquidity, beta, market capitalization, and GDP growth were used as control variables. The results revealed that debt-to-equity had no statistically significant impact on NAV during the research period, contrary to prior findings. In contrast, interest rates had a highly significant effect.

Alennus tai preemio nettovarallisuusarvoon (NAV) on tunnettu ilmiö, jossa listattuja kiinteistöyhtiötä hinnoitellaan alle (alennus) tai yli (preemio) niiden NAV:in. Tämä viittaa siihen, että epäsuora markkina kokee yhtiön alle olevien kiinteistöjen olevan vähemmän tai enemmän arvokkaita kuin suora markkina. Useiden tekijöiden tiedetään vaikuttavan NAV arvostukseen, mutta tämä tutkielma keskittyy miten velka ja korot vaikuttavat siihen. Nämä muuttujat ovat merkittäviä, koska velan hyödyntäminen on keskeinen osa kiinteistöyhtiöiden liiketoimintaa, ja korkotasot vaikuttavat suoraan velkapääomamarkkinoihin ja siten yritysten velkatasoihin. Vaikka aiempi tutkimus on osoittanut negatiivisen yhteyden velan ja NAV-alennuksen välillä, todisteita korkotason vaikutuksesta on vähän, eikä Ruotsin listattuja kiinteistömarkkinoita ole äskettäin tutkittu. Tämä tutkielma koostuu kirjallisuuskatsauksesta ja empiirisestä tutkimuksesta. Kirjallisuuskatsaus tarkastelee olennaisia tutkimuksia NAV-alennuksesta ja siitä, mitkä tekijät ovat osoittautuneet siihen vaikuttaviksi, kuten velka, likviditeetti, markkina-arvo ja markkinatunnelma. Lisäksi kirjallisuuskatsaus käsittelee suorien ja epäsuorien kiinteistöjen arvostamista, jotta lukija ymmärtää, miten yrityksen NAV-arvo määritetään. Empiirisessä analyysissä käytetään kiinteiden vaikutusten regressiomallia tutkimaan velan ja korkotason vaikutuksia NAV:iin. Muiden vaikutustekijöiden huomioon ottamiseksi käytettiin kontrollimuuttujina likviditeettiä, beta-kerrointa, markkina-arvoa ja BKT-kasvua. Tulokset osoittivat, että velan ja oman pääoman suhde ei ollut tilastollisesti merkitsevä NAV:in suhteen tarkastelujakson aikana, mikä poikkeaa aiemmista havainnoista. Sitä vastoin korkotasoilla oli erittäin merkittävä vaikutus.
Keywords: discount to NAV, net asset value, real estate, NAV-alennus, nettovarallisuusarvo, kiinteistö